2007
DOI: 10.1007/s10695-007-9157-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zinc on cadmium induced haematological and biochemical responses in a freshwater teleost fish Catla catla

Abstract: The haematological (Hb, RBC, WBC) and biochemical (protein and glucose) profiles of a freshwater fish Catla catla were studied under sub-lethal toxicity of cadmium chloride for 25 days (Treatment I). In addition, the influence of zinc on cadmium toxicity was investigated for haematological and biochemical parameters (Treatment II). In both the experiments, blood haemoglobin and plasma protein level decreased in the treated fish. However, WBC, RBC and plasma glucose levels were increased in Treatment I, while T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…Our results revealed that both plasma total protein and albumin levels were significantly decreased in fish exposed to the highest concentration (100 mg/l) of pyrene (P o0.05). A decline in plasma total protein and albumin levels caused by stressors such as pharmaceuticals Saravanan et al, 2011), PAHs (Salman, 2011;Okwu et al, 2014;Osman et al, 2009), heavy metals (Lavanya et al, 2011;Sathya et al, 2012;Remyla et al, 2008) and pesticides (Banaee et al, 2011;Saravanan et al, 2011) was also noted in previous studies. Different mechanisms have been proposed to explain the reduction in plasma total protein and albumin, which include mobilization of proteins to meet energy demands, liver cirrhosis or kidney nephrosis (loss of protein from the plasma into urine due to increased glomerular permeability), alteration in enzymes responsible for protein biosynthesis, oxidative damage to protein molecules caused by PAH-derivative oxidants, disturbance in the synthesis of amino acids due to elevated plasma cortisol level, and synthesis of lipoproteins for tissue repair (Ghosh and Chatterjee, 1989;Sathya et al, 2012;Kavitha et al, 2010;Van der Boon et al, 1991;Okwu et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Our results revealed that both plasma total protein and albumin levels were significantly decreased in fish exposed to the highest concentration (100 mg/l) of pyrene (P o0.05). A decline in plasma total protein and albumin levels caused by stressors such as pharmaceuticals Saravanan et al, 2011), PAHs (Salman, 2011;Okwu et al, 2014;Osman et al, 2009), heavy metals (Lavanya et al, 2011;Sathya et al, 2012;Remyla et al, 2008) and pesticides (Banaee et al, 2011;Saravanan et al, 2011) was also noted in previous studies. Different mechanisms have been proposed to explain the reduction in plasma total protein and albumin, which include mobilization of proteins to meet energy demands, liver cirrhosis or kidney nephrosis (loss of protein from the plasma into urine due to increased glomerular permeability), alteration in enzymes responsible for protein biosynthesis, oxidative damage to protein molecules caused by PAH-derivative oxidants, disturbance in the synthesis of amino acids due to elevated plasma cortisol level, and synthesis of lipoproteins for tissue repair (Ghosh and Chatterjee, 1989;Sathya et al, 2012;Kavitha et al, 2010;Van der Boon et al, 1991;Okwu et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Zn ?2 is a competitive ion for Cd ?2 and prevent the toxic effect of this metal (Shaffi et al 2001). Zn ?2 is an essential trace element and its role in animal and human health has been well documented for many years ago Remyla et al 2008). Zn ?2 involves in many enzyme activities, animal growth, immune function, reproduction and also development of all major organ system (Paterson et al 1991;Moshtaghie and Badii 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with this evidence, other authors described that metals may cause reactive oxygen species (ROS) production and, in turn, cell and DNA damage, impaired mitochondrial respiration, cell cycle arrest and apoptosis in various biological models [52,53,54,55]. Hence, the overall consideration is that the effect of metals such as Zinc, Cadmium, Cobalt and Lanthanum on biological substrates may be heterogeneous, also owing on the variety of the in vitro models used for toxicity assays [38,56,57,58]. …”
Section: Discussionmentioning
confidence: 99%